الحقوق الاجتماعية والسياسية لذوي الإعاقة في الشريعة الإسلامية = Social and political rights of persons with disabilities in Islamic law - Ahmad Abdallahi AlAli, Fatimah; Arif, Arif Ali (IIUM Press, International Islamic University Malaysia, 2020)
يهدف هذا البحث إلى بيان حقوق المعوقين الاجتماعية والسياسية، خاصة في ظل ازدياد أعداد المعوقين، وجهل بعض شرائح المجتمع بحقوقهم وحاجاتهم، مما يسبب لهم الاهمال والعسر، ويؤدي بهم إلى العزلة، وهي أمور يرفضها ديننا الإسلامي، ويعتمد البحث المنهج الاستقرائي، حيث يتتبع شواهد اهتمامات الشريعة الإسلامية في المراجع الفقهية والاجتماعية، والمنهج التحليلي، وذلك بتحليل نصوص الأحكام الشرعية من خلال استقراء الحقوق، وقد أفردت لهم حقوق خاصة بهم، واشتركوا مع غيرهم من الأسوياء في حقوق، ورفع عنهم الحرج في حقوق أخرى، وهذا ما يبينه البحث، فمحاوره تدور حول الحقوق الاجتماعية، وما يتفرع عنها من حقوق، كحق التكافل الاجتماعي، وحق التنقل، وحق التأهيل، وكذلك الحقوق السياسية، وما يندرج تحتها، و ما يتفرع عنها، كحق الجنسية والمواطنة، وحق القضاء، وحرية التعبير، وحق الانتخاب والشورى، وبيان أن الأشخاص ذوي الإعاقة لهم حق التمتع بهذه الحقوق مالم يُعفوا منها، وأنهم شركاء مع غيرهم فيها. وأما محاور البحث فتتضمن مبحثان. ******************************************************************************* This research aims at identifying social and political rights of disabled. Especially, with the consideration of increasing in number of disabled and ignorance of some people in the society about their rights and needs, which cause them neglect and hardship and lead them to isolation, all which are rejected by Islam. The inductive method is used in the research to find the evidence in jurisprudential and social references on the concern of Islamic Shariah about the issue, as well as analytical approach, by analyzing the texts of Islamic rules through the extrapolation of the rights. Indeed, disabled has been given some special rights, and other common public rights, as hardship has been lifted on him regarding some other rights. These are the areas to be identified in this research. Therefore, the study revolves around the social rights and its contents, such as: the right to social solidarity, right to freedom of movement, right to rehabilitation and qualification, as well as the political rights and its contents, such as the right of nationality and citizenship, judicial right, freedom of expression and the right to vote and to be member of Shura Council. Likewise, the statement that disabled is entitled to the enjoyment of these rights as others, unless they are exempted by the law.